Sharing local knowledge - Muilerman, Sander; Schläpfer, Juanita; Tisselli, E. (2013)
Researchers now use information & communications technology (ICT) to gather information more effectively from the field. Sander Muilerman, Juanita Schläpfer and Eugenio Tisselli discuss how ICTs can also give them the possibility to help share knowledge in local communities.